Periodization of Mongolian Literature in the 20th century - Galbayar, G. (Acta Mongolica, 2005)
About 100 years old Mongolian literature in the 20th century has been one important theoretical and historical subject, which formed it’s own method, appearance, figure and artistic standard. The main research purpose of any science is to determine the rule of the researching object. Science of literary study is to study deeply the development and change of the features of literature; to analyze and sum up theoretically and historically how it influences to the social individual’s mind and how it’s mysterious and complicated nature is explained. Many scholars have agreed that it’s suitable to periodize when analyzing and summing up a certain author’s creature or the history of development and change of any literature. Therefore its very important question to periodize the Mongolian literature in the 20th century on the basis of the theory and history of science.